1978
DOI: 10.2105/ajph.68.6.557
|View full text |Cite
|
Sign up to set email alerts
|

Manganese pollution in the city environment and its relationship to traffic density.

Abstract: As lead is phased out of gasoline, other additives with anti-knock properties, particularly organic manganese compounds, are being substituted. Unavoidably, such compounds go through the combustion process, are eliminated in exhaust gases, and become part of the city environment. To obtain some indication of the extent of this new pollution, street soils from various locations in a heavily trafficked city (Newark, NJ) were analyzed for manganese and lead by atomic absorption. Highly significant inverse relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…Data on chemical mixtures in humans are limited only to a few studies (88)(89)(90). Animal studies have demonstrated increased spontaneous motor activity among rats with joint Mn/Pb exposures relative to those with only one metal (91) 52 [e2] .…”
Section: Metal Mixtures and Neurodevelopmentmentioning
confidence: 99%
“…Data on chemical mixtures in humans are limited only to a few studies (88)(89)(90). Animal studies have demonstrated increased spontaneous motor activity among rats with joint Mn/Pb exposures relative to those with only one metal (91) 52 [e2] .…”
Section: Metal Mixtures and Neurodevelopmentmentioning
confidence: 99%
“…According to the literature [5] 10 -15 up to 30% of manganese added as MMT is emitted at the tailpipe. Relating this emission rate to the concentration of MMT in regular unleaded gasoline makes the combustion of MMT a major (16.9 mg/l), source of inorganic manganese in the troposphere [4,6,7]. It is therefore important to obtain mechanistic and kinetic data pertinent to the interaction of manganese with two major atmospheric oxidants ozone and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…29 It has been stated that the combustion of MMT may be one of the main sources of inorganic Mn contamination in the urban environment, particularly in areas of abundant traffic. 19,30,31 This contamination may have led to an increase in inorganic Mn, as was the case with Pb from gasoline. 11,32,33 The Toronto Manganese Personal Exposure study, carried out by the Research Triangle Institute in 1995-1996 and reported in 1998, showed that airborne Mn resulting from the combustion of MMT was not entering the Canadian environment at atmospheric levels that could constitute a health risk.…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition, the location of the sites may have influenced the results. For example, site E +1 was slightly elevated in position and densely covered with mixed hardwoods, unlike site E +2 .…”
mentioning
confidence: 99%